THE HISTORY OF THE DIPODOIDEA (RODENTIA, MAMMALIA) IN THE MIOCENE OF ASIA: 6. LOPHODONT LOPHOCRICETINAE - Zazhigin V.S.; Lopatin A.V. (My University, 2002)
Two new lophocricetine genera from the Mio-Pliocene of the southern part of Western Siberia and Kazakhstan are established. Sibirosminthus gen. nov. includes four species, which are characterized by large sizes and clearly lophodont molars: S. seletyensis sp. nov. (MN13), S. latidens sp. nov., S. irtyshensis sp. nov. (MN13-MN14), and S. betekensis sp. nov. (MN15). Sibirosminthus probably originated from the genus Lophocricetus, namely, from the lineage L. (L). vinogradovi-L. (L). grabaui. Lophosminthus gen. nov. includes two species, L. savinovi sp. nov. (MN12/MN13) and L. fugax sp. nov. (MN13). These forms are relatively small and display only weakly developed lophodonty. Lophosminthus originates from one of the most advanced Late Miocene forms of the genus Heterosminthus, which was similar to H. saraicus.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен